Religionsfreiheit als heilsame Provokation: Dankesrede anlässlich der Verleihung des Alfons Auer-Ethik-Preises - Bielefeldt, Heiner (Theologische Quartalschrift, 2018)
Freedom of religion or belief radiates the aura of a "classical" human right: it is wellestablished, deeply anchored in legal standards and widely recognized. At a closer look, however, freedom of religion or belief harbours provocative potential for state, society and Church. Against authoritarian state interventions, it demarcates a legally protected sphere of religious freedom. Within liberal society, freedom of religion or belief may serve as a reminder that freedom is not just a lifestyle issue; it may incur existential demands. For religious communities, including the Catholic Church, religious freedom can become a bridge to encounter and critically appreciate the modern ethos of freedom.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Alfons auer; Ethos of freedom; Freedom of religion; Human rights